The origins of California's gun violence restraining order law: a case study using Kingdon's multiple streams framework - Elizabeth A. Tomsich; Veronica A. Pear; Julia P. Schleimer; Garen J. Wintemute (BMC, 2023)
Abstract Background Firearm violence is a major public health problem in the United States, yet most states lack a mechanism to temporarily remove firearms from individuals who are at high and imminent risk of harming themselves or others and are not otherwise prohibited. Extreme risk protection order (ERPO) laws are intended to close this gap. The current study examines the passage of California's gun violence restraining order (GVRO) bill using Kingdon's multiple streams framework. Methods This study was based on an analysis of interview data from six key informants involved in the passage of the GVRO legislation. Results Findings indicate policy entrepreneurs framed the problem and designed the policy to target individuals at behavioral risk of imminent firearm violence. Policy entrepreneurs comprised an integrated policy network that engaged in a lengthy period of collaboration and bargained with interest groups to yield a bill that satisfied diverse concerns. Conclusions This case study may inform efforts in other states to pass ERPO policies and other firearm safety laws.